Social Desirability Response Effects: Three Alternative Models - Ganster, Daniel C.; Hennessey, Harry W.; Luthans, Fred (Academy of Management Journal, 1983)
Three models are developed for the effects of social desirability (SD) on organizational behavior research results. SD can act as (a) an unmeasured variable that produces spurious correlations between study variables, (b) a suppressor variable that hides relationships, or (c) a moderator variable that conditions the relationship between two other variables.